Factors influencing english listening comprehension in foreign language department classrooms (advanced II courses, semester I 2012) - García Gómez, José Martín
Communication has two dimensions: speaking (expression), and listening (reception). Among the basic skills we need for success in life, listening is primary. Today, we know the importance of being good listeners, which not only enable us to be more efficient students or employees, but also give us the capability to build good interpersonal relations. Becoming a good listener make us more sensitive to the needs of the listener and hence, improve our competence as a speaker. It also makes us more sensitive to the needs of people in general. In the following chapters, this paper discusses the factors that influence English listening comprehension in Foreign Language Department classrooms. The paper states twenty factors as main obstacles that interfere in listening for comprehension. The study was carried out on the Advanced English courses of the Foreign Language Department. Students were assessed with a brief listening test taken from the TOEFL Preparation exam (Cambridge University Press, Third Edition). A survey gives us the perception of how often students feel affected by each of the twenty factors. Results and recommendations of the research are of significance and may prove beneficial to English language teaching in Foreign Language Department.